2017
DOI: 10.1016/j.nmni.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a novel Enterobacter kobei clone carrying chromosomal-encoded CTX-M-12 with diversified pathogenicity in northeast China

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…According to the ANI results of 977 ECC genomes retrieved from the NCBI RefSeq database, the four species ( E. cloacae , E. hormaechei , E. roggenkampii , and E. kobei ) accounted for 82.7% of ECC population studied in this work, and most genomes were clinically associated, suggesting that the four species were predominant in the clinical setting. This is consistent with the previous studies ( Zhou et al., 2017 ; Davin-Regli et al., 2019 ; Wang et al., 2020 ). It is meaningful to develop a method which can identify ECC organisms efficiently and differentially, and has the potential to aid the control of four major ECC infections greatly.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…According to the ANI results of 977 ECC genomes retrieved from the NCBI RefSeq database, the four species ( E. cloacae , E. hormaechei , E. roggenkampii , and E. kobei ) accounted for 82.7% of ECC population studied in this work, and most genomes were clinically associated, suggesting that the four species were predominant in the clinical setting. This is consistent with the previous studies ( Zhou et al., 2017 ; Davin-Regli et al., 2019 ; Wang et al., 2020 ). It is meaningful to develop a method which can identify ECC organisms efficiently and differentially, and has the potential to aid the control of four major ECC infections greatly.…”
Section: Discussionsupporting
confidence: 94%
“…Another important member of ECC is E. kobei . Clinical strains of E. kobei have been isolated from various clinical samples, including blood, sputum, urine, bronchoalveolar lavage, abscesses, and especially intra-abdominal samples ( Zhou et al., 2017 ; Davin-Regli et al., 2019 ). A recent study showed that E. hormaechei and E. kobei were the predominant ESBL-positive species accounting for more than 70% of community-acquired ECC strains collected across China ( Zhou et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical significance of these strains is often uncertain. However, the species is now also of concern because of ESBL production (80).…”
Section: Enterobacter Cloacae Complexmentioning
confidence: 99%
“…These species are regularly isolated from clinical material and are involved in the development of opportunistic infections ( Raro et al., 2019 ; Arabaghian et al., 2019 ; Araujo et al., 2021 ). Likewise, Enterobacter species can cause opportunistic infections in human and animals ( Davin-Regli, Pagès, 2015 ; Zhou et al., 2017 ; Büyükcam et al., 2018 ; Annavajhala et al., 2019 ; Fuentes-Castillo et al., 2021 ). Citrobacter europaeus , isolated in this study from soil and dust samples of the intensive traffic area; was first isolated from the feces of a diarrheal patient and described in 2017 ( Ribeiro et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%